Educational Camp for Girls: Fostering Interest in Reading, Science and Technology with Extension Projects - Carvajal Alfaro, Vanessa (2025)
This study addresses the issue of gender inequality in areas such as science, technology, and education, where girls, especially in rural areas of Costa Rica, are poorly represented. The main objective was to promote interest in reading, science, and technology among girls in the community of Sarapiquí, helping to reduce gender gaps in these fields. To achieve this, an educational camp was designed and executed, including workshops on reading, optics, and robotics. The methodology used combined a constructivist approach and the STEAM pedagogical model, which advocates the integration of the disciplines of science, technology, engineering, arts, and mathematics. The 90-minute workshops encouraged active learning, experimentation, and group reflection. The results show an increase in the participation of girls in scientific and technological activities, strengthening their skills in robotics, optics, and reading comprehension. Furthermore, the activities enhanced the development of teamwork and critical thinking skills. A positive impact on the self-esteem and empowerment of the girls was highlighted, as they showed greater confidence in their scientific and technological abilities. In addition, the importance of an inclusive approach that challenges gender stereotypes and promotes equity in education was stressed. Conclusions show that educational projects like this one are fundamental for reducing gender gaps in science and technology, as they promote meaningful and transformative learning for young participants